PENGARUH HARGA, KUALITAS PRODUK DAN PROMOSI (PERSONAL SELING) TERHADAP KEPUTUSAN PEMBELIAN PRODUK SPAREPART MESIN PACKAGING DI UD. ANSTECH SIDOARJO - Rosyida, Deva Aulianie; Maruta, Anom; Ida Pratiwi, Ni Made (Research Journal of Social Science and Economics, 2025)
ABSTRACT Price, product quality and promotion are important forms that exist throughout the company. The primary objective of this research is to ascertain the level of influence that pricing exerts on consumers’ purchasing choices of packaging machine spare parts products at UD. Anstech Sidoarjo, how significant is the impact of the quality of a product on consumer purchasing choices holds significant sway packaging machine spare parts at UD. Anstech Sidoarjo, how significant is the influence of promotion (personal selling) on purchasing decisions for packaging machine spare parts products at UD. Anstech Sidoarjo. The focus of this study revolves around individuals who engage in consumer activities buy packaging machine spare parts products After gathering responses from a diverse group of 100 individuals, a non-probability sampling method (specifically, non-random sampling) was employed. This technique is taken using respondents with certain criteria. The measurement uses a Likert scale and the data collection used is the E-Questionnaire or gform. Based on the findings of this research, it can be inferred that the buying choices are influenced in a favorable and noteworthy manner by factors such as pricing, product quality, and promotional activities for packaging machine spare parts products at UD. Anstech Sidoarjo. This Based on the t test outcomes that have been examined, it becomes evident studied by researchers.